2022
DOI: 10.1097/dcr.0000000000002523
|View full text |Cite
|
Sign up to set email alerts
|

Omentoplasty in Patients Undergoing Abdominoperineal Resection After Long-Course Chemoradiation for Locally Advanced and Locally Recurrent Rectal Cancer: A Comparative Single-Institution Cohort Study

Abstract: BACKGROUND: Omentoplasty is a commonly performed procedure after abdominoperineal resection for rectal cancer, but its effectiveness to reduce pelviperineal complications is not firmly established. OBJECTIVE: This study aimed to assess the impact of omentoplasty on postoperative outcomes after long-course (chemo) radiotherapy and abdominoperineal resection in patients with locally advanced and locally recurrent rectal cancer. DESIGN: Retrospective cohort study. SETTINGS: Single center. PATIENTS: All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Although the impact of omentoplasty on surgical procedures has been extensively studied 3 8 , 13 , there is a lack of comprehensive studies that summarize all procedures and conduct subgroup analyses based on age and BMI. Both factors have significant implications for various postoperative outcomes 108 112 , necessitating further subgroup analysis to inform clinical decision-making. This is the first investigation into the current utilization of omentoplasty across a spectrum of procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Although the impact of omentoplasty on surgical procedures has been extensively studied 3 8 , 13 , there is a lack of comprehensive studies that summarize all procedures and conduct subgroup analyses based on age and BMI. Both factors have significant implications for various postoperative outcomes 108 112 , necessitating further subgroup analysis to inform clinical decision-making. This is the first investigation into the current utilization of omentoplasty across a spectrum of procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies also show that it does not reduce the rates of small bowel obstruction and perineal complications. [13], [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, all of these have limitations in terms of technical considerations, costs, operative times, and issues related to the placement of foreign bodies like prostheses, meshes, and balloons. Moreover, the success rates with the available techniques are far from satisfactory, and there seldom resulted in frightful complications [7], [8], [10]- [13]. Moreover, the risk of perineal wound complications like infection, dehiscence, and delayed healing following abdominoperineal resection ranges from 14% to 80 % [14], [15] To mitigate many of the concerns with the available methods, we propose using a partially mobilised urinary bladder with umbilical ligaments hitched to the pelvic inlet as an effective barrier to avoid the descent of the small bowel into the low pelvis.…”
Section: Introductionmentioning
confidence: 99%
“…Van Campenhout et al 16 reported a single-center study to assess the effect of "omentoplasty" on the incidence of pelvic and perineal complications following long-course neoadjuvant chemoradiation for LARC and abdominoperineal resection. Ingwersen et al 17 used data from the 2011-2020 Dutch Colorectal Audit to assess the declining use of diverting stomas in rectal cancer surgery and the impact on anastomotic leak.…”
Section: Technical Aspects Of Surgery Effects Of Treatment On Surgery...mentioning
confidence: 99%